2011
DOI: 10.1002/bin.336
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Joint Attention to Children with Autism Through A Sibling‐Mediated Behavioral Intervention

Abstract: Joint attention is pivotal to the development of complex social skills and language, and many individuals with Autism Spectrum Disorders display deficits in this domain. Behavioral interventions targeting joint attention are evidenced to be effective in teaching these skills to young children with autism, but these treatments have traditionally been implemented by adults in structured settings. Concerns regarding the generalizability of skills acquired under such conditions have been raised. Four typically dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0
16

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 43 publications
4
57
0
16
Order By: Relevance
“…In the study, the social validity findings collected from the mothers for subjective evaluation revealed that their opinions regarding the social interaction skills were positive. The findings of this study show consistency with the findings of the previous studies in which behavior modification techniques (Celiberti & Harris, 1993), social interaction behaviors (Oppenheim-Leaf et al, 2012;Tsao & Odom, 2006), imitation skills (Walton & Ingersoll, 2012), and joint-attention skills in home environments (Ferraioli & Harris, 2011) were taught.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In the study, the social validity findings collected from the mothers for subjective evaluation revealed that their opinions regarding the social interaction skills were positive. The findings of this study show consistency with the findings of the previous studies in which behavior modification techniques (Celiberti & Harris, 1993), social interaction behaviors (Oppenheim-Leaf et al, 2012;Tsao & Odom, 2006), imitation skills (Walton & Ingersoll, 2012), and joint-attention skills in home environments (Ferraioli & Harris, 2011) were taught.…”
Section: Discussionsupporting
confidence: 81%
“…Taking into account the game choices of the participants and using iPad game stories as games made this study different from other studies. Game sets were used as teaching materials in other studies (Ferraioli & Harris, 2011;Oppenheim-Leaf et al, 2012;Walton & Ingersoll, 2012). Moreover, feedback in this study regarding the performance displayed by the participants has been presented differently when compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al provide insufficient evidence to draw such a radical conclusion. Although unusual eye gaze behavior is well-documented in individuals with autism [22,23], a tremendous amount of research has demonstrated that joint attention, eye contact, and eye gaze abnormalities can be ameliorated with existing research-based interventions and improvements in these behaviors are, in fact, associated with improvements in communication, social skills, and other desirable outcomes [24][25][26].…”
Section: Somamentioning
confidence: 99%